Does depletion have a bright side? Self‐regulation exertion heightens creative engagement. Issue 2 (23rd November 2021) - Ho, Cony M.; Lin, Szu‐Han ( Joanna); Johnson, Russell E.
Abstract: Resource‐based theories posit that exerting self‐control to regulate one's thoughts, feelings, and behaviors depletes people's available self‐regulatory resources, leaving them depleted and less able to exert self‐control in subsequent activities. Although the detrimental effects of depletion are well‐established, we challenge this prevailing view by proposing that depletion can have unexpected beneficial effects. Across multiple studies, our current research provides evidence that depletion shifts consumers' attention on benefits of creativity, and in turn influences their subsequent creative engagement. Specifically, we found that depletion increases consumers' persistence in creative activity, and this beneficial effect of depletion on creative engagement is explained by their attention on benefits of creativity. Furthermore, we explore a boundary conditions of this depletion‐creative engagement effect by demonstrating that the effect could be attenuated for individuals who are not open to new experiences.